Four high sensitivity troponin assays and mortality in US adults with cardiovascular disease: The national health and nutrition examination survey, 1999-2004 - John W. McEvoy; Dan Wang; Olive Tang; Michael Fang; Chiadi E. Ndumele; Josef Coresh; Robert H. Christenson; Elizabeth Selvin (Elsevier, 2024)
Objective: High sensitivity cardiac troponin (hs-cTn) may be useful to monitor residual risk in secondary prevention. Our objective was to study the correlations and comparative associations with mortality of four hs-cTn assays in US adults with known cardiovascular disease (CVD). Methods: We studied 1,211 adults with a history of CVD who participated in the National Health and Nutrition Examination Survey (NHANES) 1999-2004. Using stored samples, we measured hs-cTnT (Roche) and three hs-cTnI assays (Abbott, Siemens, and Ortho). Outcomes were all-cause and CVD mortality, with follow-up through December 31, 2019. Results: Mean age was 64 years, 48 % were female, and 80 % identified as non-Hispanic White. Pearson's correlation coefficients between hs-cTn assays ranged from 0.67 to 0.85. There were 848 deaths (365 from CVD). Among adults with a history of prior non-fatal CVD, each hs-cTn assay (log-transformed, per 1-SD) was independently associated with CVD death (HRs ranging from 1.55 to 2.16 per 1-SD, all p-values <0.05) and with all-cause death (HRs ranging from 1.31 to 1.62 per 1-SD, all p-values <0.05). Associations of hs-cTnT and all-cause and CVD death remained significant after adjusting for hs-cTnI (and vice versa). Associations between hs-cTnI and CVD death remained significant after mutually adjusting for other individual hs-cTnI assays: e.g., HR 2.21 (95 % CI 1.60, 3.05) for Ortho (hs-cTnI) after adjustment for Siemens (hs-cTnI) and HR 1.81 (95 % CI 1.35, 2.43) for Ortho (hs-cTnI) after adjustment for Abbott (hs-cTnI). Conclusion: In US adults with a history of CVD, we found modest correlations between 4 hs-cTn assays. All assays were associated with all-cause and CVD mortality. The hs-cTnT assay was associated with mortality independent of the hs-cTnI assays. Hs-cTnI assays also appeared to be independent of each other. Thus, hs-cTn assays may provide distinct information for residual risk in secondary prevention adults.